A room-temperature magnetic semiconductor from a ferromagnetic metallic glass - Wenjian Liu (Nature Portfolio, 2016)
Magnetic semiconductors provide control of spin states in addition to charge states realized in conventional semiconductors, yet currently limited to weak magnetism at low temperature. Liuet al. introduce oxygen into a ferromagnetic metallic glass, resulting in a Curie temperature above 600 K.